2021
DOI: 10.3389/fimmu.2021.688674
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome-Induced Osmotic Pressure and the Mechanical Mechanisms Underlying Astrocytic Swelling and Membrane Blebbing in Pyroptosis

Abstract: Cell swelling and membrane blebbing are characteristic of pyroptosis. In the present study, we explored the role of intracellular tension activity in the deformation of pyroptotic astrocytes. Protein nanoparticle-induced osmotic pressure (PN-OP) was found to be involved in cell swelling and membrane blebbing in pyroptotic astrocytes, and was associated closely with inflammasome production and cytoskeleton depolymerization. However, accumulation of protein nanoparticles seemed not to be absolutely required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Astrocyte pyroptosis involves cell swelling, pore formation in the cell membrane and increased membrane permeabilization ( Chen et al, 2016 ; Zheng et al, 2021 ). The present study found that FMPH high dose co-treatment significantly inhibited olanzapine-, quetiapine-, risperidone-, or haloperidol-induced increased expression of NLRP3, caspase-1, GSDMD and IL-1β.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Astrocyte pyroptosis involves cell swelling, pore formation in the cell membrane and increased membrane permeabilization ( Chen et al, 2016 ; Zheng et al, 2021 ). The present study found that FMPH high dose co-treatment significantly inhibited olanzapine-, quetiapine-, risperidone-, or haloperidol-induced increased expression of NLRP3, caspase-1, GSDMD and IL-1β.…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact mechanism by which antipsychotics induce pore formation is unknown. A recent study in astrocytes reported that activated GSDMD increased osmotic pressure (OP) and intracellular calcium, and these effects contributed to astrocyte swelling and membrane blebbing ( Zheng et al, 2021 ). Additional studies that investigate the effects of antipsychotics on OP and calcium flux and whether these effects are related to GSDMD are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 F). In addition, IF tension is closely associated with OP alteration [ 13 , 14 , 38 ], and JK and Tax co-treatment could partly improve IF tension caused by AngII, while JK, Tax, or both had no effect on the BK model (Fig. 1 G).…”
Section: Resultsmentioning
confidence: 99%
“…Water metabolism and edema occurrence depend on transmembrane oncotic pressure gradients in the body [ 13 ]. Based on a recent study, protein nanoparticle production can result in increased osmotic pressure (PN-OP) and water flow, which is also thought to involve upregulation of membrane fluidity and promotes nonselective permeability [ 14 , 15 ]. Previous studies suggested that ARDS is associated with the secretion of proinflammatory cytokines and inflammasome production [ 1 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%